Time reversal in polarized neutron decay: the emiT experiment (2000)
The standard electro-weak model predicts negligible violation of time-reversal invariance in light quark processes. We report on an experimental test of time-reversal invariance in the beta decay of polarized neutrons as a search for physics beyond the standard model. The emiT collaboration has measured the time-reversal-violating triple-correlation in neutron beta decay between the neutron spin, electron momentum, and neutrino momentum often referred to as the D coefficient. The first run of the experiment produced 14 million events which are currently being analyzed. However, a second run with improved detectors should provide greater statistical precision and reduced systematic uncertainties.